ASSOCIATION OF BODY MASS INDEX WITH MORTALITY AMONG STROKE HAEMORRAGIC PATIENTS - Meida Laely Ramdani; Sri Yani (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Abnormal body mass index (BMI) that leads to obesity and overweight is a problem that must be considered. It was one of the major health problems in the worldwide. Obesity and overweight contribute to risk factor for stroke and contribute to rapid death than those in normal BMI. The aim of this study was to analyse the association of Body Mass Index (BMI) with mortality among haemorrhagic stroke patients in the Unit Stroke, RSUD Banyumas. Non-experimental with retrospective approach has been used on this study. Total of 111 respondents using total sampling technique was taken from the medical record data of the Banyumas hospital from November 2018 to November 2019. Chi-square analyses has been performed to analyse this data. The statistical analysis showed that hemorrhagic stroke patients who died within ?48 hours were 55 respondents (49,5%) and those who died within ? 48 were 56 respondents (50,5%). Abnormal BMI  (?25 kg/m2) were 46 patients (41,4%) and normal BMI (<25 kg/m2) were 65 respondents (58,6%). The chi square result obtained p value= 0,045 with OR 2,2189.  Which means that there was a relationship between BMI and mortality among hemoragic stroke.